Factors Influencing Financial Performance of Agricultural Companies Listed in Nairobi Securities Exchange in Kenya - Masavi, Justus Moki (My University, 2018)
This study sought to determine the factors influencing financial performance of agricultural companies listed in Nairobi Securities Exchange (NSE). The objectives of the study were to establish the target capital structure of agricultural companies listed in NSE, to ascertain the effect of turnover on financial performance of the agricultural companies listed in NSE and to assess the effect of Board Size on financial performance of the agricultural companies listed in NSE. The study adopted longitudinal research design with targeted population being the six agricultural companies listed in NSE. Secondary data was obtained from published financial statements for the period 20102014. Desk research instrument was used to obtain the data. Census was carried on the six companies listed in the NSE. The empirical data on factors influencing financial performance was analyzed using the Statistical Package for Social Sciences (SPSS), to establish the relationship between the variables for study. Pearson’s Correlation Coefficient was determined and Multivariate Regression Analysis was used to determine the factors influencing the financial performance of the agricultural companies listed in NSE in Kenya. The findings of this study showed that an increment in debt ratio led to reduction in financial performance, and the reduction in financial performance following an increment in debt ratio would be large to guarantee a significant change in the after tax profits of the companies. An increase in turnover will led to an increment in financial performance, and the increment in financial performance following an increment in turnover will be large to guarantee a significant change in the after tax profits of the companies. Board size had no reasonable effect on financial performance. Based on the results it is therefore recommended that for better financial performance, there should be proper management of debt. It also recommend the growth of sales and focus on growth opportunities to increase revenue through sales. Board size should not be factored as it has little impact on financial performance of agricultural companies.
Keywords: Acquisitions; Shareholders; Companies; Kenya